Non-accidental injury of vision organ in children - Grałek, Mirosława; Moll, Agnieszka; Niwald, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Non-accidental injuries (intentionally inflicted) arise as a result of physical harm, they represent 5% of all injuries of the vision organ and often coexist with other symptoms of child abuse (battered child syndrome). Most often, the age of the physical abuse of children does not exceed 3, although it may affect children at any period of life. Non-accidental injuries related with the vision organ directly affect the eyeball and orbit or may result in head injury. Especially serious visual complications arise in infants, due to damage of the retina and optic nerve in the shaken baby syndrome. Symptoms of the child abuse also include Münchhausen syndrome by proxy, in which the caregivers of the child report symptoms of non-existent diseases on his behalf and demand their treatment. Non-accidental injuries of the vision organ require differentiation between accidental injuries and pediatric diseases with similar symptomatology.